Use of Ceftolozane/Tazobactam in a Case of Septic Shock by Puerperal Sepsis. (29th May 2019) - Pezzi, Mario; Scozzafava, Anna Maria; Giglio, Anna Maria; Vozzo, Renata; Casella, Patrizia Dina; Tiburzi, Simona Paola; Cosco, Lucio; Verre, Mario
Abstract : Multiresistant bacteria infections cause widespread morbidity and mortality and lead to an increase in expenses for hospital stays and complications. We describe the case of a 27-year-old patient with puerperal sepsis after cesarean section due to Escherichia coli complicated by multiresistant Klebsiella ESBL-producing superinfection with septic shock and multiple organ dysfunction syndrome, successfully treated with ceftolozane/tazobactam.